Desy Nurcahyanti POTENSI WILAYAH SEBAGAI KARAKTER VISUAL DALAM DESAIN BATIK GIRILAYU - Desy Nurcahyanti; Agus Sachari; Achmad Haldani Destiarmand (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
The 4.0 industrial revolution currently offers traditions. Those offer options for chose to survive, join, or merge.Various forms of technology are offering unnecessity because the community has a system and local wisdomthat keeps the form of tradition in its place. One of tradition form that’s facing on offer is batik in Girilayu.Pattern character basic on regional potencies as a characteristic of Girilayu’s batik design. Meanwhile, thespecific purpose of this research is explaining the background of batik designers in Girilayu when makingdesign development, to expose and promote the regional character in the 4.0 industrial revolution era today.The focus of the research problem includes changes and design innovations carried out by Girilayu’s batikdesigners, within the last three years, from 2016 until the middle of 2019. The research method used qualitativewith a hermeneutic approach through findings that shows visual characters of Girilayu batik. That appearedas a representation of Girilayu’s community still maintains cultural nobility by exploring regional potenciesas batik’s characteristic.